Can Peer Review Be Kinder? Supportive Peer Review: A Re-Commitment to Kindness and a Call to Action. (April 2022) - Clase, Catherine M.; Dicks, Elizabeth; Holden, Rachel; Sood, Manish M.; Levin, Adeera; Kalantar-Zadeh, Kamyar; Moore, Linda W; Bartlett, Susan J.; Bello, Aminu K.; Bohm, Clara; Bridgewater, Darren; Bouchard, Josee; et al.
Peer review aims to select articles for publication and to improve articles before publication. We believe that this process can be infused by kindness without losing rigor. In 2014, the founding editorial team of the Canadian Journal of Kidney Health and Disease (CJKHD) made an explicit commitment to treat authors as we would wish to be treated ourselves. This broader group of authors reaffirms this principle, for which we suggest the terminology "supportive review."